Numerical modeling of cyclic stress-strain behavior Of sn-pb solder joint during thermal fatigue - Tamin, M N; Liew, Y B (Universiti Kebangsaan Malaysia, 2005)

(untitled)
This study examines the cyclic stress-strain response of solder joints in a surface mounted electronic assembly due to temperature cycles. For this purpose, a threedimensional model of an electronic test package is analyzed using finite element method. The model consists of 92 solder joints arranged along the peripheral of a 24x24 solder array. The various different materials considered in the simulation are Si-die, 60Sn-40Pb solder alloy, Cu-traces, Cu6Sn5 intermetallics, FR-4 substrate and PCB. The temperature- and strain-rate-dependent plastic stressstrain curves define the viscoplastic response of the near-eutectic solder alloys. Orthotropic behavior of the FR-4 substrate and PCB is modeled. Other materials are assumed to behave elastically with temperature-dependent material properties. Temperature loading of the package consists of an initial cooling down from the re-flow temperature at 183 oC to 25 oC followed by thermal cycling between -40 to 125 oC. Results of the analysis show that the package warps with a magnitude of 93 Âµm at 25 oC after re-flow. In this process, the critical solder joint accumulated an inelastic strain of 0.856 percent. Faster temperature ramp rate at 370 oC/min (load case TR1) versus 33 oC/min (load case TC1) resulted in 12 percent lower inelastic strain after completing 3 temperature cycles. However, the inelastic strain magnitude is achieved in a much shorter time. The shear stressstrain hysteresis loops display the largest strain ranges compared to other stressstrain components. The calculated shear strain range is 0.8 percent with the corresponding stress range of 34.0 MPa.